The Civil War as a theological crisis - Noll, Mark A., 1946- (Steven and Janice Brose lectures in the Civil War era., 2006)
Although Christian believers agreed that the Bible was authoritative and that it should be interpreted through commonsense principles, there was rampant disagreement about what Scripture taught about slavery. This book tells how most Americans were radically divided in their interpretations of what God was doing in and through the Civil War.